Control interno y su incidencia en la administración de los activos fijos de la empresa Orecao S.A., del cantón Quevedo, año 2012 - Iza Puruncaja, Johanna Carolina (2015)
This research is an Internal Control and its Impact on Fixed Assets Management Company S.A. ORECAO Year 2012.The research topic was chosen based on the need in the company of an evaluation by an internal control, and according to the results takes feguard measures that benefit and resource optimization Company, According to the results of an Internal Control Fixed Assets , findings were detected , then specific to manage mentre commendations for each case is provided , considering a model of immediate solution conducting an internal control that allows you to protect and safeguard the institution a la set , verify accounting data and safeguard the assets of the company , in order to assess the level of effectiveness, efficiency and economy achieved by it in the use of available resources , identify possible hort comings , according to the general principles of good management , facilitating decision- making for persons with supervisor y responsibilities or ability to take corrective actions. Establish potential risks to which the administration defined in a broader sense as a processed effected, reliability of administrative information and to enhance confidence in compliance with the laws and regulations that apply face which in summary can help an entity get to where you want to go and avoid hazards, assess risks and measure the impact; immediately adopting criteria to improve administrative systems. Finally it is important to achieve success; one must start from a simple and effective organization involving the participation of all who make up the company.